2000
DOI: 10.1093/ndt/15.3.402
|View full text |Cite
|
Sign up to set email alerts
|

The function of permanent vascular access

Abstract: The radiocephalic and the humerobasilic a-v fistulae are the two types of VA with the longest duration of function, although a high rate of initial failure is seen with the radiocephalic a-v fistula. Age, female gender, presence of diabetic nephropathy, start of dialysis with a catheter, and failure to wait for initial maturation of the VA are risk factors, and account for the majority of VA failures during RRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
3
18

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 21 publications
6
70
3
18
Order By: Relevance
“…The most frequent clinical problem is that this access has a higher primary failure rate when compared to BCF or BBF (Miller, 1999). However, if a RCF matures, the 5 to 10 year cumulative patency rate is 53 and 45 percent respectively (Bonalumi, 1982, Rodriguez, 2000. Placement of a lower arm fistula is desirable as it preserves the upper arm for future use.…”
Section: Radial-cephalic Fistulamentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent clinical problem is that this access has a higher primary failure rate when compared to BCF or BBF (Miller, 1999). However, if a RCF matures, the 5 to 10 year cumulative patency rate is 53 and 45 percent respectively (Bonalumi, 1982, Rodriguez, 2000. Placement of a lower arm fistula is desirable as it preserves the upper arm for future use.…”
Section: Radial-cephalic Fistulamentioning
confidence: 99%
“…If a fistula is not maturing by 6 weeks, many algorithms suggest a vengram by 6 weeks. If collateral vessels are identified they may be coiled by interventional radiology techniques or ligated by surgical techniques (Rodriguez, 2000). Prevention of early fistula thrombosis with pharmacologic intervention has been the subject of several recent trials, which have shown only minimal effect.…”
Section: Early Failure/complicationsmentioning
confidence: 99%
“…The radiocephalic and the humerobasilic AVF are the two types of VA with the longest duration of function, although a high rate of initial failure is seen with the radiocephalic AV fistula [141]. It is the preferred VA on account of the longest duration, its low complications rates and its ease of puncture [142][143][144].…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…It also shoed that more than two-thirds of patients in whom the first VA developed successfully did not have any subsequent VA failure, whereas initial failure increased the risk of subsequent failure. Female gender and presence of diabetes were risk factors related to VA failure [141]. The effort to create fistula first, has successfully increased the prevalence of AVFs [147].…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…Several studies suggested a significant correlation between female gender and decreased patency rates in AVFs, as well as prolonged maturation time before the fistula can be used adequately to sustain HD sessions [20,23,26]. A combination of female gender and increased age (> 65) has been shown to be significantly associated with non-maturation when compared to men of the same age group [22,24]. However, several other studies found no significant association between female gender and high risk of AVF non-maturation [22,25,27].…”
Section: Introductionmentioning
confidence: 99%